"Sometimes the whole map is red": applying geographical assessment methods to safeguard adolescents from harm in communities. Issue 1 (16th December 2019) - Lloyd, Jenny
Abstract : Purpose: The purpose of this paper is to explore the opportunities of geographical child protection assessment methods for adolescents victimised in extra-familial contexts. Design/methodology/approach: Presenting empirical evidence from an action research study within one child protection service in the UK, the study draws upon qualitative data from practice observations, case review, training and five context assessments. Findings: Safety mapping and neighbourhood observations provide options to assess extra-familial contexts. Findings reveal that these methods support practitioners to build local knowledge of areas supporting interventions into community places rooted in principles of child protection. Research limitations/implications: While geographical methods are already used by the police to map the locations of crimes, these methods provide opportunities to account for young people's own experiences of harm and support interventions into neighbourhood spaces supporting a contextual safeguarding approach to adolescent harm. Practical implications: The paper highlights the need for further testing of contextual safeguarding approaches and policy guidance that outlines whose role it is to protect children in communities. Social implications: Geographical assessment methods provide a route to engage with young people's lived experience of place. And develop interventions that target contexts and not just individuals affected by extra-familial harm. Originality/value: The paper presents original research into the use of geographical assessment methods to be used within a child protection framework.